(untitled) (In situ, 2024)
Systematic excavations of Kozja peć on the island of Dugi otok began in 2022, after several short trial excavation campaigns aimed at determining its archaeological potential. The cave is located in the middle of the island at a height of about 200 meters above sea level, about a kilometer northwest of the entrance to the radar station on Vela straža. The excavations were carried out as part of the EpiC project of the Croatian Science Foundation (IP-2019-04-6115). They are currently carried out in an area of 20 m2, which should be enough for undisturbed work on deeper layers. The excavation defined 12 levels of walking surfaces that show the cultural image recorded in the trench. Only medieval and post-medieval finds are almost completely lacking, but finds with the characteristics of antiquity start to appear almost from the beginning.